The Influence of Perceptions of Price, Quality of Service, Ease of Use and Consumer Satisfaction on Purchasing Interest Online Shopping - Afriani, Rizki Tri; Yanti, Sunalia Risma; Hermawati, Ratu Diana (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to determine the factors that influence interest in online shopping by using independent variables such as price perception, service quality, and ease of use, and using predictor variables, namely consumer satisfaction. This research focuses on consumers who shop online from various platforms by distributing questionnaires via social media with a sample of approximately 150 people using a non-probability sampling technique. Data collection methods use observation and literature study. This research used data processing techniques using the Structural Equation Model (SEM) based on Partial Least Square (PLS) version 3.0.